2019
DOI: 10.1016/j.plabm.2019.e00116
|View full text |Cite
|
Sign up to set email alerts
|

Analytical evaluation of the Radiometer AQT90 FLEX βhCG assay

Abstract: ObjectivesMany hospitals cannot afford an hCG assay on a central lab analyzer and turn to point of care testing (POCT) solutions. The Radiometer AQT90 FLEX is a small benchtop immunoareement between the AQT90 and comparator methods for samples with hCG ssay analyzer for use in the laboratory or at the patient bedside. This study evaluated the analytical performance of the AQT90's βhCG assay.MethodsPrecision was assessed using whole blood patient samples and two levels of quality control. Linearity was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…One sample with an βhCG value > 1,000,000 IU/L gave the similar result of >5000 IU/L on AQT 90. Our results, in accordance with those previously obtained [ 15 ], confirm the manufacturer’s claim of no hook when βhCG concentrations up to 233,000 IU/L are measured.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…One sample with an βhCG value > 1,000,000 IU/L gave the similar result of >5000 IU/L on AQT 90. Our results, in accordance with those previously obtained [ 15 ], confirm the manufacturer’s claim of no hook when βhCG concentrations up to 233,000 IU/L are measured.…”
Section: Discussionsupporting
confidence: 93%
“…The performances and diagnostic accuracy of the assay were found to be clinically acceptable. The within-lab imprecision was less than 4% and comparable to previously reported CVs of 3.5-3.9% and 2.8-5.1% for level 1 and level 2 QC material, respectively [15]. The present study confirmed a positive bias evaluated at 10% compared to the Roche Elecsys hCG + β method on a e602/cobas 8000 analyzer [15].…”
Section: Analytical Performancessupporting
confidence: 90%
See 2 more Smart Citations
“…Ortho Vitros 3600/5600/ECi 0.998 14 The Radiometer AQT90 method is based on an all in one dry chemistry concept, CE certified using whole blood samples, with a volume 0.3 -2ml, with a total assay time of 18 minutes and a working range of 1 -5,000 IU/L. The agreement or concordance of the Radiometer AQT90 was 69% with the Abbott i-STAT, 81% with the Beckman Coulter and 75% with the Roche methods [15].…”
Section: Methods Correlation (R 2 )mentioning
confidence: 99%